2005
DOI: 10.1097/01.pec.0000186427.07636.fc
|View full text |Cite
|
Sign up to set email alerts
|

Preprocedural Fasting State and Adverse Events in Children Receiving Nitrous Oxide for Procedural Sedation and Analgesia

Abstract: Seventy-one percent of patients undergoing ED procedural sedation and analgesia with N2O did not meet established fasting guidelines. In this series, there was no association between preprocedural fasting and emesis. There were no serious adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 34 publications
2
35
0
1
Order By: Relevance
“…It is likely that the risk of aspiration during procedural sedation differs from that during general anesthesia involving tracheal intubation or other airway manipulations. 259,260 However, the absolute risk of aspiration during elective procedural sedation is not yet known; the reported incidence varies from ∼1 in 825 to ∼1 in 30 037. 95,127,129,173,244,261 Therefore, standard practice for fasting before elective sedation generally follows the same guidelines as for elective general anesthesia; this requirement is particularly important for solids, because aspiration of clear gastric contents causes less pulmonary injury than aspiration of particulate gastric contents.…”
Section: Dietary Precautionsmentioning
confidence: 99%
“…It is likely that the risk of aspiration during procedural sedation differs from that during general anesthesia involving tracheal intubation or other airway manipulations. 259,260 However, the absolute risk of aspiration during elective procedural sedation is not yet known; the reported incidence varies from ∼1 in 825 to ∼1 in 30 037. 95,127,129,173,244,261 Therefore, standard practice for fasting before elective sedation generally follows the same guidelines as for elective general anesthesia; this requirement is particularly important for solids, because aspiration of clear gastric contents causes less pulmonary injury than aspiration of particulate gastric contents.…”
Section: Dietary Precautionsmentioning
confidence: 99%
“…There are few published studies with adequate statistical power to provide guidance to the practitioner regarding safety or risk of pulmonary aspiration of gastric contents during procedural sedation. [104][105][106][107][108][109] When protective airway reflexes are lost, gastric contents may be regurgitated into the airway. Therefore, patients with a history of recent oral intake or with other known risk factors, such as trauma, decreased level of consciousness, extreme obesity, pregnancy, or bowel motility dysfunction, require careful evaluation before administration of sedatives.…”
Section: Before Emergency Sedationmentioning
confidence: 99%
“…It is likely that the risk of aspiration during procedural sedation differs from that during general anesthesia involving tracheal intubation or other airway manipulation. 104,105 However, because the absolute risk of aspiration during procedural sedation is not yet known, guidelines for fasting periods before elective sedation should generally follow those used for elective general anesthesia. For emergency procedures in children who have not fasted, the risks of sedation and the possibility of aspiration must be balanced against the benefits of performing the procedure promptly (see below).…”
Section: Dietary Precautionsmentioning
confidence: 99%
“…The nausea/vomiting with N 2 O is dose-and duration-dependent (>10-15 minutes after administration). [24][25][26] Some authors have reported delayed vomiting with N 2 O, and caregivers should be informed that this can occur post-discharge. 25 Vasovagal syncope was described in 1 case report included in this review with IN dexmedetomidine.…”
Section: Practical Considerationsmentioning
confidence: 99%
“…[24][25][26] Some authors have reported delayed vomiting with N 2 O, and caregivers should be informed that this can occur post-discharge. 25 Vasovagal syncope was described in 1 case report included in this review with IN dexmedetomidine. 18 The clinical significance of vasovagal syncope and other adverse events associated with dexmedetomidine administered through this route is unknown.…”
Section: Practical Considerationsmentioning
confidence: 99%